(untitled) (TAMADDUN NURI JURNALI, 2024)
In this article, the concept of political belief, its essence, formation, and components are analyzed philosophically, and its role in shaping political processes is investigated. The impact of political beliefs on an individual or group’s perspectives on political issues, systems, and ideologies is examined. Additionally, the role of political beliefs in shaping perceptions of political processes in society and their influence on people’s participation in these processes are analyzed.